The methods and practices in grants regarding loans and advances recovery in private commercial bank: Southeast Bank Limited - Arefin, Mir Sohanuzzaman (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.